Chitosan coated magnetic cellulose nanowhisker as a drug delivery system for potential colorectal cancer treatment - Mostafa, Yusefi; Shameli, Kamyar; Soon, Michiele Lee Kiun *; Teow, Sin Yeang; Moeini, Hassan; Roshafima, Rasit Ali; Pooneh, Kia; Jie, Chia Jing; Nurul Hidayah, Abdullah (Elsevier, 2023)
Polysaccharide-based magnetic nanocomposites can eminently illuminate several attractive features as anticancer drug carriers. In this study, rice straw-based cellulose nanowhisker (CNW) was used as solid support for Fe3O4 nanofillers to synthesize magnetic CNW. Then, cross-linked chitosan-coated magnetic CNW for 5-fluorouracil carrier abbreviated as CH/MCNW/5FU. Fourier-transform infrared, X-Ray diffraction, and X-ray photoelectron spectroscopy analysis indicated successful fabrication and multifunctional properties of the CH/MCNW/5FU nanocomposites. In addition, CH/MCNW/5FU nanocomposites showed hydrodynamic diameter and zeta potential value of 181.31 ± 3.46 nm and +23 ± 1.8 mV, respectively. Based on images of transmission electron microscopy, magnetic CNW as reinforcement was coated with chitosan to obtain almost spherical CH/MCNW/5FU nanocomposites with an average diameter of 37.16 ± 3.08. The nanocomposites indicated desired saturation magnetization and thermal stability, high drug encapsulation efficiency, and pH-dependent swelling and drug release performance. CH/MCNW/5FU nanocomposites showed potent killing effects against colorectal cancer cells in both 2D monolayer and 3D spheroid models. These findings suggest CH/MCNW as a potential carrier for anticancer drugs with high tumour-penetrating capacity.